Pengaruh Intensitas Cahaya Terhadap Fotosintesis Dan Pertumbuhan Tanaman Bayam (Amaranthus Sp) - Putri Harta Bawamenewi (CV. SINAR HOWUHOWU, 2025)
This study aims to determine the effect of light intensity on the photosynthetic rate and growth of spinach plants (Amaranthus sp.). The research was conducted experimentally using a Completely Randomized Design (CRD) with one treatment factor: light intensity consisting of four levels—100% (P1), 75% (P2), 50% (P3), and 25% (P4) of natural sunlight. Observed parameters included photosynthetic rate, plant height, number of leaves, leaf area, fresh weight, and dry weight. The results showed that light intensity significantly affected all observed variables. The highest photosynthetic rate (18.5 μmol CO₂/m²/s), plant height (22.4 cm), number of leaves (18), fresh weight (35.2 g), and dry weight (5.7 g) were obtained under full sunlight (P1). In contrast, the lowest values were recorded under 25% light intensity (P4). It can be concluded that higher light intensity enhances photosynthetic activity and vegetative growth of spinach plants significantly. Therefore, managing appropriate light levels is crucial for optimal spinach cultivation, especially in controlled or indoor farming systems.